10th Edition! Happy birthday Archives of Pediatric Neurosurgery! - de Oliveira, Ricardo Santos (2022)
The first edition of the Archives of Pediatric Neurosurgery (APN) was released in September 2019. Since then we have completed the 10th edition. There were 108 submissions receives (44/year), with a rejection rate of 20%. Archives of Pediatric Neurosurgery is the first open access electronic-only journal in pediatric neurosurgery, and also we are on social media as Facebook, Instagram and Tweeter.  APN is the only journal specialized in Pediatric Neurosurgery in Latin America and Mexico.                We have different types of publication highlighted the original papers, review, clinical case, video clinical case, and clinical video lecture. The Archives of Pediatric Neurosurgery is a triannual peer-reviewed medical online journal and was recognized in September 2020 as the official publication of the Brazilian Society for Pediatric Neurosurgery. In addition, the internal regulation (by-laws) was approved during the 2021 SBNPed Business Meeting.    Some statistics related to APN (2019-2022):   MOST DOWNLOADED PDF ARTICLE: Dezena et al. Anatomy of the ventricular system: Historical and morphological aspects MOST READ ABSTRACT: De Paula et al. Shaken Baby Syndrome: literature review in the last 5 years MOST CITED ARTICLE: de Oliveira RS, Ballestero MFM.  The Covid-19 Outbreak and Pediatric Neurosurgery guidelines All articles are available online and free license to open access and download. All the papers were peer-reviewed (Figure 1). During this period, we included a specialized consultancy and we were able to index the APN in several indexing bases: DOAJ, Google Scholar, Cengage, REDIB, Crossref, Dimensions, J-Gate, and BASE.                DOAJ is the most important community-driven, open access service in the world and has a reputation for advocating best practices and standards in open access. DOAJ indexing has brought recognition of a correct and well-structured work On this special occasion the editorial office would like to extend their greatest appreciation to all editors, and reviewers who have been supportive, and devoted much of their time and effort in nurturing APN. The journal, in particular, would like to thank the authors for submitting their papers to APN. We organized two editions in 2022 focusing on craniofacial and arachnoid cysts. Based on data from Google Analytics, APN is gaining momentum and attracting interest from readers. The number of accesses to abstracts has been increasing progressively since 2019 (Figure 1). The editorial board thanks you and the work continues so that we can reach new indexing bases and consolidate as a reference in pediatric neurosurgery. Recently, the Brazilian Neurosurgery Society recognized the importance of APN by supporting the project.                Happy Birthday Archives of Pediatric Neurosurgery! A long life for everyone!